2014
DOI: 10.1177/1060028014546361
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Monitoring in Antiphospholipid Syndrome and Lupus Anticoagulant

Abstract: In a subgroup of APS patients, INR monitoring may not be safe for determining the dose of warfarin because their INR values can be falsely elevated. Although CFX monitoring is more accurate, it too comes with its own downsides. Managing warfarin therapy in the APS population needs to be individualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…This study has demonstrated that despite the challenges encountered with the PT/INR system when establishing anticoagulant intensity in APS patients [5,6], the majority of thrombotic APS patients on long term warfarin display no differences in INR between two commonly used thromboplastin reagents, Innovin® and PT-Fib HS+. However, in a proportion of APS patients, the PT/INR system appears to lose utility Table 1 Patients showing INR discrepancies between PT reagents Results for all patients with ≥0.5 INR unit discrepancy between Innovin and PT-Fib HS+ in APS and non-APS patients are shown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study has demonstrated that despite the challenges encountered with the PT/INR system when establishing anticoagulant intensity in APS patients [5,6], the majority of thrombotic APS patients on long term warfarin display no differences in INR between two commonly used thromboplastin reagents, Innovin® and PT-Fib HS+. However, in a proportion of APS patients, the PT/INR system appears to lose utility Table 1 Patients showing INR discrepancies between PT reagents Results for all patients with ≥0.5 INR unit discrepancy between Innovin and PT-Fib HS+ in APS and non-APS patients are shown.…”
Section: Discussionmentioning
confidence: 98%
“…Monitoring warfarin anticoagulation in patients with antiphospholipid syndrome (APS) poses additional challenges [5,6]. These patients inherently differ from other thrombotic patients by virtue of their antiphospholipid antibodies (aPL), particularly lupus anticoagulant (LA) and anti-prothrombin antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The patient number in some studies was only small [12,13], and the results are conflicting. Moreover, because CFX assays were until recently costly and not widespread in use, the therapeutic range of anticoagulant therapy has not been properly evaluated [15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with APS have an increased risk of thrombotic events, and the main therapeutic goal is precisely to prevent such events; thus, patients with this condition require anticoagulation for long periods of time,2 4 either as primary or secondary prevention, and warfarin is currently the drug of choice in non-pregnant patients 3 4…”
Section: Discussionmentioning
confidence: 99%
“…The current therapeutic INR target in patients with APS, according to the anticoagulation guidelines of the American College of Chest Physicians (CHEST), is between 2.0 and 3.0 5. However, the recommendations are not clear for patients with APS who are positive for LA, in whom the risk of thrombosis is higher, as these antibodies mediate the activation of platelets, monocytes and endothelial cells, causing an inflammatory process that alters the natural anticoagulant and fibrinolytic system 3. Some authors have questioned the targets set by CHEST due to the limitations and lack of statistical significance of the clinical trial supporting this recommendation, which is categorised as Grade 2B 3…”
Section: Discussionmentioning
confidence: 99%